YOU ARE NEVER ALONE AS A LITERARY TRASH? - Pavel Matejovič (Slovenska Literatura, 2009)
The author deals with interpretation of Mináč´s prose Nikdy nie si sama (You Are Never Alone), published in 1962. He also pays attention to wider discussion appeared in literary magazines in 1962-1963 concerning that literary double-novelette. He stressed the significance of the critical reaction of Bohuš Kováč´s critical achievement exceptional in the historical context of the first half of the 60-tieth. It was comparable with critical articles and polemics of M. Hamada. B. Kováč pointed out a problem of genre classification of Mináč´s literary works, which in 50–tieth and 60-tieth had a form of exemplary, popular literature (tradition of literature in calendars). That way he created a platform for overlapping of both the types of literature in the area of genre and values. The mentioned problem becomes the central theme also in the author´s study. He comes out from the semiotic and cultural analyses of U. Ecco from the first of the 60–tieth. They have several common parallels with Kováč´s critical argumentation. The author of the study was also inspired by the works of Czech literary theorists and historians (D. Mocná, P. Janáček). They pointed out some genre – typological similarities between Social Realism and popular literature. The author came to conclusion that Mináč ´s double novelette Nikdy nie si sama (You Are Never Alone) is a typical example of “socialist midcult“ performing mainly ideological functions, while aesthetic function was suppressed. That Mináč´s auctorial intention was clearly identifiable mainly in the end of his prose, in which he comes back to constructional poetics typical for the 50-tieth. It is also the most problematic dimension of his prose. Mináč attempted to make that part interesting through motifs of sentimental and erotic literature (those motifs were there to draw attention of the readers). Altogether with ideological facture those auctorial courses created a genre hybrid.